Modulations of resting-static functional connectivity on insular by electroacupuncture in subjective tinnitus - Zha, Bixiang; Zhang, Yating; Shi, Feifei; Cheng, Ling; Rong, Zhihao; Yu, Leiyu; Liu, Wanting; Xue, Qiuju; Ye, Min; Yang, Jinying; Qiu, Bensheng; Yang, Jun (Frontiers in Neurology, 2024)
Objective To explore the modulations of electroacupuncture in subjective tinnitus (ST) by comparing the difference of functional connectivity (FC) in ST patients and healthy volunteers between the insular (INS) and the whole brain region. Methods A total of 34 ST patients were selected into electroacupuncture group (EG) and 34 age- and sex-matched normal subjects were recruited into control group (CG). The EG received acupuncture at SI19 (Tinggong), GB11 (Touqiaoyin), TE17 (Yifeng), GV20 (Baihui), GV15 (Yamen), GV14 (Dazhui), SJ13 (Zhongzhu), among which the points of SI19 and GB11 were connected to the electroacupuncture instrument with the density wave of 2/50 Hz, and 3 treatments per week for 10 sessions in total. The severity of tinnitus was evaluated by Tinnitus Handicap Inventory (THI), the hearing status was recorded using pure tone audiometry, and resting-state functional magnetic resonance imaging (rs-fMRI) was performed on the brain before and after treatment, the CG received no intervention yet only rs-fMRI data were collected. Results With the electroacupuncture treatment, the total THI score, average air conduction threshold of patients of EG were significantly lower than before (p < 0.01), and the total effective rate was 88.24%. Compared with CG, FC of ST patients between INS and left superior temporal gyrus and right hippocampal significantly decreased before treatment, while FC of ST patients between INS and right superior frontal gyrus, left middle frontal gyrus and right anterior cuneus significantly decreased after treatment (voxel p < 0.001, cluster p < 0.05, corrected with GRF). FC of ST patients between the INS and right middle frontal gyrus, left superior frontal gyrus and right paracentral lobule showed a significant decrease after treatment (voxel p < 0.001, cluster p < 0.05, corrected with GRF). In addition, THI score in EG was negatively correlated with the reduction of FC value in INS-left superior frontal gyrus before treatment (r = −0.41, p = 0.017). Therefore, this study suggests that abnormal FC of INS may be one of the significant central mechanisms of ST patients and can be modulated by electroacupuncture. Discussion Electroacupuncture treatment can effectively reduce or eliminate tinnitus symptoms in ST patients and improve the hearing by decreasing FC between the INS and the frontal and temporal brain regions.